THE EFFECTIVENESS OF GLUTEUS ACTIVATION AND CORE STABILITY FOR PATIENTS WITH LOW BACK PAIN: A LITERATURE REVIEW - Niam, Muhammad Azka; Aditya, Ivan Fairuz; Yulianti, Dwi; Silmi, Roidha; Rahman, Nurrozaan Hanif; Akasi, Oriza Junio; Pristianto, Arif (CV. Fahr Publishing, 2025)
Low back pain (LBP) is a musculoskeletal pain condition in the lumbosacral area, located below the costal margin and above the inferior gluteal fold, commonly caused by unhealthy lifestyle habits and body mass index. This study aimed to examine the effectiveness of gluteus activation exercise and core stability exercise in patients with low back pain symptoms. The method involved administering trunk exercises in the form of core stability exercise (CSE), which is emphasized as a universal physiotherapy approach to optimize movement, transfer, pressure control, and activity performance. In addition, hip exercises in the form of gluteus activation were applied to activate weakened gluteal muscles due to prolonged static positions, which may lead to gluteal muscle alterations, thereby increasing the risk of lower extremity injuries and low back pain. The analysis showed that patients with low back pain who received gluteus activation intervention experienced a greater reduction in pain by -1.70 units compared to those who received trunk exercise (SMD = -0.46; 95% CI = -0.46 to 0.12), with results statistically significant (p < 0.00001). The heterogeneity of the studies was high (I² = 81%, random effects model). Conclusion: Gluteus activation exercise proved to be more effective in reducing low back pain compared to core stability exercise among patients with low back pain symptoms.